Association Between Fatigue and Motor Exertion in Patients With Multiple Sclerosis—a Prospective Study - Drebinger, Daniel; Rasche, Ludwig; Kroneberg, Daniel; Althoff, Patrik; Bellmann-Strobl, Judith; Weygandt, Martin; Paul, Friedemann; Brandt, Alexander U.; Schmitz-Hübsch, Tanja (Frontiers in Neurology, 2020)
Background: Fatigue in multiple sclerosis (MS) is conceived as a multidimensional construct. Objectives: To describe changes of balance and gait parameters after 6-minute walking (6MW) as potential quantitative markers for perceptions of state and trait fatigue in MS. Methods: 19 patients with MS (17 with fatigue) and 24 healthy subjects underwent static posturography, gait analysis and ratings of perceived exertion before and after 6MW. Results: 6MW was perceived as exhaustive, but both groups featured more dynamic comfortable speed walking after 6MW. Shorter stride length at maximum speed and increased postural sway after 6MW indicated fatigability of balance and gait in MS group only. While most changes were related to higher levels of perceived exertion after 6MW (state fatigue), higher fatigue ratings (trait fatigue) were only associated with less increase in arm swing at comfortable speed. Further analysis revealed different associations of trait fatigue and performance fatigability with disability and motor functions. Performance fatigability was most closely related to EDSS while for trait fatigue strongest correlations were seen with balance function and handgrip strength. Conclusions: Fatigability of performance was closely related to perceptions of exertion after 6MW (state fatigue) and disability in MS, but distinct from fatigue ratings, conceived as trait fatigue. Our study identified postural sway, arm swing during gait and hand grip strength as unexpected potential motor indicators of fatigue ratings in MS.